Development of a responsive web-based digital library for geography education students - Prihadi, Adhitya; Permana, Ryan (Jurnal Kajian Informasi dan Perpustakaan, 2024)
A responsive web-based digital library is an application built with web technology to allow users to access digital collections via the Internet. Most digital libraries have not adequately addressed the need for self-directed learning for students, so students' access to educational resources is still limited. This study aimed to determine the development of a responsive web-based digital library for geography education students through an analysis of the identification of the planning process for a responsive web-based digital library, a feasibility evaluation by experts, and an assessment of geography education students’ responses. The research method used a Research and Development strategy through the 4D model (define, design, develop, and disseminate). The result was that the research plan involved needs analysis for students. The system design used case and activity diagrams and prototype development validated by experts. Expert evaluation on usability, navigation, graphic design, content, and compatibility falls in the 62.50% < score ≤ 81.25% range, indicating feasibility. The study result was a research plan involving needs analysis for geography education students. The system design used case and activity diagrams and the development of a prototype validated by experts. Expert evaluations on usability, navigation, graphic design, content, and compatibility were in the range of 62.50% < score ≤ 81.25%, indicating feasibility. Students' responses showed that the highest percentages were visual communication (80.73%, very good), usability (76.03%, good), and device compatibility (78.18%, good). In conclusion, this study provides significant contributions to supporting self-directed learning by providing easier access to academic resources for geography education students.